Application of thermally coupled energy levels in Er3+ doped CdMoO4 phosphors: Enhanced solid-state lighting and non-contact thermometry. (September 2019) - Ran, Weiguang; Noh, Hyeon Mi; Park, Sung Heum; Lee, Bo Ram; Kim, Jung Hwan; Jeong, Jung Hyun; Shi, Jinsheng
Graphical abstract: Highlights: Enhanced emission intensity in high temperatures has been achieved. Er 3+ doped CdMoO4 phosphor has a potential application in solid-state lighting. High sensitivity indicates that CdMoO4 : 0.02Er 3+ phosphor can be used in non-contact thermometer. Excellent water stability of Er 3+ doped CdMoO4 can be used in a complex condition. Abstract: Er 3+ -activated CdMoO4 phosphors were prepared by a traditional high-temperature solid-state method. The crystal structure, photoluminescence (PL) characteristics and performance in non-contact thermometry of as-prepared phosphors were studied in detail. Benefiting from the 3D network structure of CdMoO4 host, the desirable green emission of Er 3+ -based phosphors were observed. Especially, based on the thermally coupled energy levels, the obtained phosphors show enhanced emission intensity in high temperatures. When applied to the temperature sensor based on the fluorescence intensity ratio (FIR), the prepared CdMoO4 :0.02Er 3+ phosphor show an excellent sensitivity (0.875% K −1 ) at 483 K. Therefore, it is demonstrated that the as-prepared Er 3+ -activated CdMoO4 phosphors have a promising potential application in both solid-state lighting and non-contact thermometry.